Midwifery Care On Pregnant Women With Early Detection of Chronic Energy Deficiency In Tm I In Pekanbaru Karya Bakti Primary Clinic 2019: Midwifery Care On Pregnant Women With Early Detection of Chronic Energy Deficiency In Tm I In Pekanbaru Karya Bakti Primary Clinic 2019 - Rina Yulviana (Institute Of Computer Science (IOCS), 2020)
Chronic Energy Deficiency (KEK) in pregnant women is still a problem in Indonesia because KEK as a condition where a person experiences nutritional deficiencies (calories and protein) that lasts long and years, with marked weight less than 40 kg or looks thin and with arm circumference or (MUAC) less than 23.5 cm. Objective: increase knowledge and insights on midwifery care for pregnant women with early detection of Chronic Energy deficiencies in Trimester I at the Pratama Karya Bakti Clinic in Pekanbaru City using the SOAP approach and documentation method. Case Method Midwifery care for pregnant women with early detection of chronic energy deficiency Trimester I by providing health education (PENKES) and supplementary foods such as milk, fruits and vegetables. Conclusion: from midwifery care to Mrs. T G2P1A0H1 age 30 years gestation 6 weeks 3 days, with early detection of chronic energy deficiency in general good condition, after midwifery care for 2 days visit to the patient the results obtained in the last study are early detection of chronic energy deficiency which can gradually both with the help of consuming additional food. Suggestion: the need for the involvement of health workers to overcome the early detection of chronic energy shortages in the city of Pekanbaru so that no more pregnant women who experience complications.